The Crisis of State Sovereignty and Social Rights - Staiano, Sandro (The Age of Human Rights Journal, 2014)
The European integration process –which may be interpreted as a federalizing process– faces strong cultural and economic resistances. As a matter of fact, social rights have been understood and performed –within an old tradition of political thought– as proximity rights that cannot be universalized beyond the context of national States; this led to the resistant ideology of the protective function of State borders. Therefore it seems that the construction of the European Union as a complete political subject cannot be developed further if a centralized European Welfare is not created.